2012
DOI: 10.1002/ejlt.201100338
|View full text |Cite
|
Sign up to set email alerts
|

Equimolar mixture of c9,t11 and t9,t11 CLA inhibits the growth and induces apoptosis in Caco‐2 cells

Abstract: In 2008, CLAs received a no-objection letter from the FDA on its generally recognized as safe (GRAS) status for certain foods. However, aside from the mixture of c9, t11-CLA and t10, c12-CLA, other CLA mixtures are still not used in food production. The effects of different concentrations (25, 50, 100, and 200 mmol/L) of CLA mixture (c9, t11-CLA and t9, t11-CLA) on the human colorectal carcinoma cell line Caco-2 cells after various treatment times (1, 2, 3, and 4 days) and the induced apoptosis were examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Caco-2 cells from passages 30 to 50 were used in all experiments and cultured as previously described. 16 After reaching subconfluence, Caco-2 cells were recovered from the culture flask through 0.25% trypsin digestion after washing twice with PBS. The medium was changed every 2 d. Cell counts based on conductivity measurements and cell viability were assessed using the trypan blue test.…”
Section: Cell Culturementioning
confidence: 99%
“…Caco-2 cells from passages 30 to 50 were used in all experiments and cultured as previously described. 16 After reaching subconfluence, Caco-2 cells were recovered from the culture flask through 0.25% trypsin digestion after washing twice with PBS. The medium was changed every 2 d. Cell counts based on conductivity measurements and cell viability were assessed using the trypan blue test.…”
Section: Cell Culturementioning
confidence: 99%
“…Other studies showed that cis-9, trans-11 CLA has extra beneficial effects, such as anti-inflammatory and anti-atherogenic effects (Ecker, Liebisch, Patsch, & Schmitz, 2009;Loscher et al, 2005). Furthermore, it has been demonstrated that the mixture of the two CLA isomers (cis-9, trans-11 and trans-9, trans-11 CLA) had a synergistic antiproliferation effect on a human colorectal carcinoma cell line (Zhong, Luo, Huang, Deng, & Lei, 2012). Interestingly, the strains of Lb.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Conjugated linoleic acid (CLA), referring to a heterogeneous group of geometrical and positional conjugated isomers of linoleic acid (LA, 18:2), has received increasing attention because of its demonstrated biological properties, including cancer inhibition [1,2,3,4], blood cholesterol lowering [5], diabetes controlling and weight loss effects [6,7]. Most of these studies, however, were carried out with CLA as free fatty acid (FFA) [4,5,6,7] and only a few studies have used CLA in the form of triacylglycerols (TAG) [8,9].…”
Section: Introductionmentioning
confidence: 99%